Evaluation of Fish Raw Materials as a Way to Increase the Information Content of its Characteristics - Safronova T.; Panchishina E.; Kraschenko V.; Karpenko Y. (Техника и технология пищевых производств, 2019)
Introduction. The research features a detailed sensory evaluation of mass fishing objects belonging to different families, namely: the Macrouridae represented by the giant grenadier (Albatrossia pectoralis), the Herrings represented by the Pacific herring (Clupea pallasii), and the Salmons represented by the Keta salmon (Oncorhynchus keta). The research objective was to study the possibility of increasing the information content of the verbal description of fish raw materials in combination with a quantitative assessment of individual sensory indicators. Research objects and methods. The paper introduces the concept of detailed verbal description of group parameters of raw and heattreated muscle tissue. The description can increase the information capacity of sensory studies. The concept of extended description of fish raw material was added to the main sensory properties that describe color, smell, taste, and consistency. They include data on the properties of local areas with subcutaneous layer, dark muscles, fat layers, etc. Such a detailed verbal description gives an in-depth view of the sensory properties, which is part of general information on the functional and technological properties of the fish and a key factor in designing new developed products. To improve the objectivity of sensory research, the authors employed the method of quantitative evaluation. Results and discussion. The results were summed up as data on the significance coefficients established by experts, ranked, and expressed as a percentage. The significance coefficient is a method of quantitative regulation of the share of each sensory indicator in the general sensory evaluation. The research showed that the greater the number of group sensory indicators that characterize the object, the smaller and more similar their coefficients of significance, which dramatically reduces application opportunities. Therefore, significance coefficient proved a convenient means of measurement and visual presentation. However, the research was limited by the experimental conditions. Conclusion. The study of the fish raw materials established, identified, and described individual sensory indicators that involved about twenty lexical units for raw material and thirty units for heat-treated muscle tissue. The individual sensory indicators characterized color, smell, and taste. They differed in the presence of several degrees of gradation and fit into a vertical three-level (sometimes two-level) classification. Group touch indicator of the consistency describes mostly single-level unit indicators with 4–6 lexical units. As a result, the detailed description of sensory properties of fish raw materials included 2–3 times more lexical units compared to the traditional description of fish raw materials in the special reference literature.